An empirical study on key factors for purchasing strategy on project based organizations: A case study of gas field development projects - Aboulfazl Kazazi; Jamshid Salehi Sadaghiyan; Sohrab Sohrabiaraghi (Management Science Letters, 2012)
One of the primary concerns in development of oil and gas resources is to find the critical success factors associated with different important projects. Purchasing and procurement plays a key role in these projects. There is no doubt that in history of similar studies, there are not much studies to determine key factors. The proposed study of this paper presents an empirical study to find these factors in one of the most important gas filed in Iran is now South Pars Gas Field. The study distributes a questionnaire consists of various questions associated with purchasing activities. We investigate the feedbacks gathered from decision makers using factor analysis. The results of our survey reveal that there are three categories of organizational strategy, the relative importance of strategy and risk according to factor analysis. Each factor consists of many other factors and the relative importance of all factors are investigated.